Cost-effectiveness evaluation based on two models of first-line atezolizumab monotherapy and chemotherapy for advanced non-small cell lung cancer with high-PDL1 expression - Zhang, Chuan; Liu, Yue; Tan, Jing; Tian, Panwen; Li, Weimin (Frontiers in Oncology, 2023)
Background: Atezolizumab may provide clinical benefits to patients with advanced non-small cell lung cancer (NSCLC). However, the price of atezolizumab is relatively high, and its economic outcomes have remained unclear. In this study, we used two models to examine the cost-effectiveness of initial atezolizumab monotherapy versus chemotherapy for patients with PD-L1 high-expressing EGFR and ALK wild-type advanced NSCLC in the context of the Chinese healthcare system. Methods: Partitioned Survival model and Markov model were performed to evaluate the cost-effectiveness of first-line single-agent atezolizumab versus platinum-based chemotherapy for patients with advanced NSCLC with PD-L1 high-expressing EGFR and ALK wild-type disease. Clinical outcomes and safety information were obtained from the most recent data from the IMpower110 trial, while cost and utility values were obtained from Chinese hospitals and relevant literature. Total costs, life years (LYs), quality-adjusted life years (QALYs), and incremental cost-effectiveness ratios (ICERs) were estimated. One-way and probabilistic sensitivity analyses were performed to explore model uncertainty. Scenario analyses were also conducted for the Patient Assistance Program (PAP) and various provinces in China. Results: In the Partitioned Survival model, the total cost of atezolizumab was $145,038, providing 2.92 LYs and 2.39 QALYs, while the total cost of chemotherapy was $69,803, providing 2.12 LYs and 1.65 QALYs. The ICER for atezolizumab versus chemotherapy was $102,424.83/QALY; in the Markov model, the ICER was $104,806.71/QALY. Atezolizumab was not cost-effective at the WTP threshold of three times China's per capita gross domestic product (GDP). Sensitivity analysis showed that the cost of atezolizumab, the utility of PFS, and the discount rate had a significant impact on ICER; PAP significantly reduced ICER, but atezolizumab was still not cost-effective in China. Conclusion: First-line monotherapy with atezolizumab for patients with PD-L1 high-expressing EGFR and ALK wild-type advanced NSCLC was estimated to be less cost-effective than chemotherapy in terms of the Chinese healthcare system; offering PAP increased the likelihood that atezolizumab would be cost-effective. In some areas of China with higher levels of economic development, atezolizumab was likely to be cost-effective. To improve the cost-effectiveness of atezolizumab, drug prices would need to be reduced.